Hepatitis B e-antigen and its correlation with other serological markers in chimpanzees. - Ling, C M (1979)
Three chimpanzees experimentally infected with hepatitis B virus, and another three chimpanzees that were hepatitis surface antigen carriers, were studied for the presence of viral antigens and humoral immune responses. Quantitative analyses of hepatitis B surface and e-antigens in sequential serum samples at early acute stages revealed cyclic oscillations of these two antigens following a synchronous pattern. Similar analyses of anti-e-antigen and anti-hepatitis B core antigen antibodies from the three experimentally infected primates indicated that peak titers of these two antibodies occurred as surface antigen decreased to undetectable levels. Of the three surface-antigen carriers, two were positive for e-antigen and one was positive for e-antigen antibody for the entire course of surveillance (8, 9, and 22 months, respectively).